Solar Radiation as an Isolated Environmental Factor in an Experimental Mesocosm Approach for Studying Photosynthetic Acclimation of Macrocystis pyrifera (Ochrophyta) - Celis-Plá, Paula S. M.; Kappes, José Luis; Figueroa, Félix L.; Pereda, Sandra V.; Villegas, Karina; Altamirano, Robinson; Hernández-González, María Carmen; Buschmann, Alejandro H. (Frontiers in Plant Science, 2021)
Solar radiation effects on the ecophysiology and biochemical responses of the brown macroalga Macrocystis pyrifera (L.) C. Agardh were evaluated using a mesocosm approach, in Southern Chile. Treatments with different radiation attenuations were simulated with three vertical attenuation coefficients: (1) total (Kd = 0.8 m-1), (2) attenuated (Kd = 1.2 m-1), and (3) low (Kd = 1.6 m-1) radiation levels. Nutrient concentration and temperature did not show differences under the three light conditions. Photosynthetic activity was estimated by in vivo chlorophyll a (Chla) fluorescence under the three light treatments, as an isolated physical factor for both in situ solar radiation in the field and under artificial blue light in the laboratory. This was achieved using two pulse amplitude-modulated (PAM) fluorometers - Diving PAM (in situ) and Junior PAM (laboratory). Photosynthetic activity and biochemical composition were measured in winter during two daily cycles (1DC and 2DC) in different parts of the plant’s thalli: (1) canopy zone, (2) middle zone, and (3) down zone, associated with different depths in the mesocosm system. Greater irradiance at midday induced a decline in the maximal quantum yield (Fv/Fm). Nevertheless, the in situ electron transport rate (ETRin situ) was higher in the exposed thalli of the canopy zone, independent of the light treatment conditions. The concentration of phenolic compounds (PC) was highest in the canopy zone under total radiation at midday in both daily cycles, and lowest in the down zone. The Chla increased in the morning under total and low radiation (1DC and 2DC). Solar radiation increasing at midday prompted the photoinhibition of photosynthesis in the canopy zone but also an increase in productivity and phenol content. Therefore, light attenuation in the water column drove key differences in the photo-physiological responses of M. pyrifera, with the highest productivity occurring in thalli positioned in the canopy zone when exposed to solar irradiance.